Dysregulated cross-talk between alveolar epithelial cells and stromal cells in idiopathic pulmonary fibrosis reduces epithelial regenerative capacity - Wisman, Marissa; Nizamoglu, Mehmet; Noordhoek, Jacobien A.; Timens, Wim; Burgess, Janette K.; Heijink, Irene H. (Frontiers in Medicine, 2023)
In idiopathic pulmonary fibrosis (IPF) constant epithelial micro-injury and aberrant interactions within the stromal micro-environment lead to abnormal alveolar repair and fibrosis. We hypothesized that alveolar epithelial regenerative responses in IPF are impaired due to disturbed crosstalk between epithelial cells and their stromal niche. We established organoid cultures from unfractionated suspensions and isolated EpCAM+ cells from distal lung tissue of patients with and without IPF. We observed significantly more organoids being formed from unfractionated suspensions compared to isolated EpCAM+ cell cultures, indicating the presence of supportive cells in the unfractionated suspensions. Importantly, lower organoid numbers were observed in unfractionated cultures from IPF lungs compared to non-IPF lungs. This difference was not found when comparing organoid formation from isolated EpCAM+ cells alone between IPF and non-IPF groups, suggesting that crosstalk between the supportive population and epithelial cells is impaired in lungs from IPF patients. Additionally, organoids grown from IPF lung-derived cells were larger in size compared to those from non-IPF lungs in both unfractionated and EpCAM+ cultures, indicating an intrinsic abnormality in epithelial progenitors from IPF lungs. Together, our observations suggest that dysregulated crosstalk between alveolar progenitor cells and the stromal niche affects the regenerative capacity, potentially contributing to alveolar impairment in IPF.